Global competencies for midwives: external cephalic version; ultrasonography, and tobacco cessation intervention. Issue 3 (June 2019) - Fullerton, Judith; Butler, Michelle; Aman, Cheryl; Reid, Tobi
Abstract: Problem and background: The International Confederation of Midwives (ICM) conducts regular updates to the Essential Competencies for Basic Midwifery Practice to determine the introduction or retention of items in the global scope of midwifery practice guidance document. Aim: This article presents the review process that underpinned the deliberation about three specific clinical practices: external cephalic version, prenatal ultrasonography, and tobacco cessation interventions that occurred during the 2016–2017 global update study. Methods: A brief outline of the research methodology used in the 2016–2017 study is provided. Literature summaries about safety and effectiveness of three clinical skills are offered. Data addressing global and regional variations in support of each practice and final disposition of the items are documented. Findings: External cephalic version did not receive sufficient document support for inclusion in the initial list of items to be tested in the study. Prenatal ultrasonography was supported as an advanced (76.6%) or country-specific (18.8%) skill that midwives could acquire, to promote wider global access for pregnant women. Midwives' participation in tobacco cessation counselling was supported (≥85%) in each of ICM's regions. Knowledge about World Health Organization recommendations for nicotine replacement therapy was endorsed as an additional (62.4%) or country-specific (29.3%) skill. Discussion and conclusion: The current evidence of safety of midwives performing external cephalic version led to the recommendation that it be considered in the next document update. Conflicting views of midwives' role in acquiring skills to conduct prenatal ultrasound were evident. There was strong support for participation in smoking cessation counselling, but knowledge of World Health Organization recommendations was not highly endorsed.